Serviceability and post-failure behaviour of laminated glass structural elements - PISCITELLI, LORENZO RUGGERO (Premio Tesi di Dottorato, 2019)
Glass structures are being built ever more frequently all over the world, in a growing architectural trend towards light, transparency and sustainability. The engineering design of laminated glass elements being profoundly influenced by properties of interlayers, this multi-scale research highlights some among the key elements on the hyperelastic and viscoplastic response of such synthetic materials. Results and new discoveries are interpreted to better model and predict the response of laminated glass structures: examples are provided for design applications to post-failure safety assessments, structural design and cold-bending techniques. Still, in a vastly unknown field, a growing market and foggy regulatory framework, many challenges and research opportunities remain to be dealt with.